Nursing Care Practices Following a Percutaneous Coronary Intervention. Results of a Survey of Australian and New Zealand Cardiovascular Nurses - Rolley, John; Salamonson, Y.; Dennison, C.; Davidson, Patricia (Lippincott Williams and Wilkins, 2009)
Background: Although there is high-level evidence to guide optimal medical care for percutaneous coronary interventions, there are less explicit guidelines to support nurses in providing care. Aim: This study describes the practice standards and priorities of care of cardiovascular nurses in Australia and New Zealand. Method: Item generation for the survey was informed by an integrative literature review and existing clinical guidelines. A 116-item Web-based survey was administered to cardiovascular nurses, via electronic mail lists of professional cardiovascular nursing organisations, using a secure online data collection system. Results: Data were collected from March 2008 to March 2009. A total of 148 respondents attempted the survey, with 110 (74.3%) completing all items. All respondents were registered nurses with an average of 12.3 (SD, 7.61) years of clinical experience in the cardiovascular setting. A range of practice patterns was ivident in ambulation time after percutaneous coronary intervention, methods of sheath removal, pain relief, and patient positioning. Respondents consistently rated psychosocial care a lower priority than other tasks and also identified a knowledge deficit in this area. Conclusion: This survey identified diversity of practice patterns and a range of educational needs. Increasing evidence to support evidence-based practice and guideline development is necessary to promote high-quality care and improved patient outcomes.